INCLUSIVE EDUCATION STRATEGIES FOR CHILDREN WITH LEARNING DISABILITIES - Darina Darbisheva (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
With many years of deep research, most of the schools have started thinking in a different way regarding the teaching methods for kids with learning disabilities. Rather than separating special kids from everyone else, the focus is on bringing them into the regular classroom atmosphere and find ways to make it work out. Education system differs around the world, however one part that unites them all is to show that every child deserves a fair shot, and that include those who are differ from their peers. This article takes a look at the kinds of strategies teachers actually use when trying to make inclusion work day to day. Things like adjusting lessons so they fit different learning styles, bringing in technology that helps kids keep up, putting together individual plans for students who need extra support, and getting kids to learn from each other in group settings